The Influence of Canva Learning Media on Economic Learning Outcomes - Arsilla, Tiara; Darmawati, Desak Made (Lembaran Ilmu Kependidikan, 2024)
Media-based learning has become the main focus of efforts to improve the effectiveness of the educational process in this digital era. Canva is a design program that acts as a learning medium, used by educators as a tool that facilitates students in digesting and understanding learning materials. With a variety of attractive templates and features, Canva helps create a creative and engaging learning environment for students. This study aims to determine the results of economic learning by using Canva learning media for class XI students of SMA 109 Jakarta. In this study, using a quantitative experimental approach, the method used was a True Experiment, and the design used was a posttest-only control group design. Sampling using saturated samples, namely the sampling method with the entire population being sampled. The instrument used in this study was a multiple-choice test sheet. The instrument measurement technique uses a multiple-choice question test that is declared valid using the Point Biserial Correlation and reliability test using KR-20 Analysis of learning outcomes u sing t-test. Data from this study using the final test given after the material has been taught to the students by using Canva learning media.  Based on the analysis results, tcount > ttable = 3.774> 2.008, so that H1 is accepted and H0 is rejected. So, the Canva learning model affects the economic learning outcomes of class XI students. The use of learning media contributes significantly to improving student learning outcomes. This research makes an important contribution in supporting the development of more effective and innovative learning strategies in the educational environment.